Study and analysis of power system stabiliser performance using artificial neural network - Magzoub, M.A. (Trans Tech Publications Ltd, 2014)
This paper represents a study and analysis of designing a PSS (Power system stabilizer) to be used with SMIB (a Single Machine and Infinite Bus) system that was developed using ANN (Artificial Neural Network). Furthermore, the dynamic performance of ANN based stabilizer is established and compared with conventional types of PSS. The proposed scheme's effectiveness was tested through simulation in order to analyse the stability features of the small signal of the system regarding the operating situation of the steady state when a transmission line is lost. The focus of the primary method was on how the control performed. This was later confirmed to possess the level of a reaching time that was shorter and a spike that was lower. Â© (2014) Trans Tech Publications, Switzerland.